In The Red The Politics of Public Debt Accumulation in Developed Countries - Barta, Zsófia (University of Michigan Press, 2018)
Why do rich countries flirt with fiscal disaster? Between the 1970s and the 2000s, during times of peace and prosperity, affluent countries-like Belgium, Greece, Italy, and Japan-accumulated so much debt that they became vulnerable and exposed themselves to the risk of default. In the past three decades, an extensive scholarly consensus emerged that these problems were created by fiscal indiscipline, the lack of sufficient concern for budgetary constraints from policy makers as they try to please voters. This approach formed the foundation for the fiscal surveillance system that attempted to bring borrowing in European countries under control via a set of fiscal rules. In the Red demonstrates that the problem of sustained, large-scale debt accumulation is an adjustment issue rather than a governance failure. Irrespective of whether the original impetus for borrowing arose from exogenous changes or irresponsible decision making, policy makers invariably initiate spending cuts and/or tax increases when debt grows at an alarming rate for several years in a row. Zsófia Barta argues that explaining why some countries accumulate substantial amounts of debt for decades hinges on understanding the conditions required to allow policy makers to successfully put into place painful adjustment measures.